Poslednie piat' let - Aizenberg, Alexander; Kaufman, Matthew King (Russia : Krupnyi Plan ; Castle Comminications PLS ; Eastern Light Productions, 1994)
This film, edited from archival footage and photographs, charts the chain of errors and musjudgements that preceded the fall of the monarchy and ultimately led to the violent death of the Romanov family in 1918. The film contains rarely shown archival film and photo materials from Krasnogorsk film archive related to the celebration of the 300 anniversary of the Romanovs, World War I, and the arrest and exile of the royal family.